Isolation and Structural Characterization of Biflavonoids from Araucaria hunsteinii and Araucaria columnaris: Chemotaxonomic and Pharmacological Perspectives - Sugita, Purwantiningsih; Ningtias, Widya Sekar Ayu; Priandanda, Rafi Chandra; Ilmiawati, Auliya; Kurniawanti, Kurniawanti; Agusta, Dhea Demitri; Dianhar, Hanhan; Rahayu, Dyah Utami Cahyaning (Jurnal Kimia Valensi, 2025)
Biflavonoids are a distinctive class of dimeric flavonoids known for their diverse biological activities and chemotaxonomic significance. In this study, two biflavonoids were isolated from the acetone extracts of Araucaria hunsteinii twigs and Araucaria columnaris leaves collected from Bogor Botanical Garden, Indonesia. Chromatographic techniques, including Sephadex LH-20 column chromatography and preparative thin-layer chromatography, were employed for purification, followed by structural elucidation using LC-MS/MS and 1D/2D NMR spectroscopy. The compounds were identified as 4',4''',7,7''-tetra-O-methylcupressuflavone (1) and 7-O-methylcupressuflavone (2). Notably, this is the first report of 7-O-methylcupressuflavone isolated from A. columnaris leaves, providing new chemotaxonomic insights into the genus Araucaria. A literature-based pharmacological analysis revealed promising cytotoxic and α-glucosidase-inhibitory activities of the isolated compounds. These findings contribute to the phytochemical profiling and highlight the pharmaceutical potential of Araucaria-derived biflavonoids.